Pengembangan Usaha Mikro Kecil Menengah (UMKM) Pada Kelompok UPPKA Sehati Melalui Branding dan Pembuatan Katalog Produk di Kelurahan Banjarsari, Surakarta - Ani Rakhmawati; Nadia Efrilia Khasanah (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This community service activity aims to develop MSMEs in RW 08 Banjarsari Village. In addition, it is also to increase the understanding of business actors about the importance of product branding as a marketing strategy. In this activity, the FKIP 01 UNS KKN Team collaborated with the UPPKA Sehati group which acts as a forum for MSMEs in RW 08 Banjarsari Village. The methods used in this activity are focus group discussions, surveys, interviews, MSME data collection through forms, and design making. The participation and enthusiasm of business actors in this activity is very good, the partner group actively contributes to the implementation of the activity from beginning to end. The result of this activity is in the form of logo branding by making logos for products from business actors who do not yet have their own logos and product catalogs for the UPPKA Sehati group.